Geographical and maximum distance on-demand routing algorithm G-MDORA - Dania Mohammed; Muhamad Mansor; Goh Chin Hock (Universitas Ahmad Dahlan, 2023)
A vehicular ad hoc network (VANET) is an intelligent technology that allows efficient communication, secure data transmission, and traffic management. VANET allows vehicles in the network to communicate wirelessly with roadside units (RSUs) or between vehicles within a coverage area. The primary goal of adopting VANET is to reduce the frequency of accidents in specific urban regions drastically. It has a significant impact on passenger safety and the ability of drivers to drive safely in metropolitan areas. As the number of cars on the road grows, so does the number of accidents. As a result, a better traffic system is required to address this issue. VANET is a cutting-edge network that primarily delivers intelligent transportation system (ITS) services to end-users to facilitate data exchange and ensure safety. In this paper, we propose geographical and maximum distance on-demand routing algorithm (G-MDORA) that combines the advantages of geographic routing protocol (GRP) and MDORA protocol for Ad hoc routing between vehicle to vehicle (V2V). Our proposed model provides an idea that can be used to improve the performance of the GRP and MDORA protocol. Moreover, the performance of the G-MDORA, GRP, and MDORA protocol was compared in terms of end-to-end delay, communication overhead, throughput, and packet loss ratio.